2011
DOI: 10.1007/s11783-010-0283-1
|View full text |Cite
|
Sign up to set email alerts
|

Freshwater algae chemotaxonomy by high-performance liquid chromatographic (HPLC) analysis

Abstract: The study of community composition of algae is essential for understanding the structure and dynamics of the aquatic ecosystem and for evaluating the eutrophic level of the water body. A high-performance liquid chromatographic (HPLC) method based on a reversephase C 18 nonpolar column was developed for the main algal taxa, which includes cyanophytes, bacillariophytes, euglenophytes, dinophytes, and chlorophytes. Based on the elution order using HPLC, 19 pigments were identified, and they were chlorophyllide a,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Complete structure evaluation was performed by many researchers to study bioactive natural products, and methods used were: 1D, 2D NMR, MS/MS, HPLC and chiral GC-MS analysis [163][164][165][166].…”
Section: Capillary Electrophoresis Using Diode Array Detection (Ce-dad)mentioning
confidence: 99%
“…Complete structure evaluation was performed by many researchers to study bioactive natural products, and methods used were: 1D, 2D NMR, MS/MS, HPLC and chiral GC-MS analysis [163][164][165][166].…”
Section: Capillary Electrophoresis Using Diode Array Detection (Ce-dad)mentioning
confidence: 99%
“…The use of this technique in freshwater is not so usual as it is marine or estuarine waters, (Descy et al., 2009;Simmons et al, 2016), but it has shown effectiveness monitoring the phytoplankton community in lakes (Fietz & Nicklisch, 2004;Descy et al, 2005;Picazo et al, 2013). HPLC allows rapid and automated analysis of lipophilic photosynthetic pigments (Jeffrey et al, 1999) with a high differentiating power of the higher taxonomic categories (Hou et al, 2011). On the other hand, microscopic techniques are able to discriminate at the level of genus or species, but present difficulties in the identification of nanoplankton and picoplankton, commonly well represented in oligotrophic systems, and also the reproducibility is lower than with chromatographic techniques (Goericke & Montoya, 1998;Fietz & Nicklisch, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…However, chemotaxonomy studies on other plants showed that chemical compounds (e.g., Sesquiterpene dialdehyde, etc) could be considered as species markers [22]. Furthermore, Hou et al [23] found that chemotaxonomic classification could be very useful for aquatic assessment in distinguishing phytoplankton communities and extremely advantageous and cost-effective in large ecosystem-scale research. Li et al [24] found that the evolution and classification of bamboos inferred from leaf wax n-alkanes were consistent with morphological investigations reported previously.…”
Section: Introductionmentioning
confidence: 99%